The pathway from childhood maltreatment to adulthood obesity: The role of mediation by adolescent depressive symptoms and BMI. (August 2018) - O'Neill, Allison; Beck, Kenneth; Chae, David; Dyer, Typhanye; He, Xin; Lee, Sunmin
Abstract: Aim: to examine associations between childhood maltreatment and adulthood obesity, and mediating effects of adolescent depressive symptoms and BMI, using the U.S. National Longitudinal Study of Adolescent to Adult Health (n = 10, 894). Individuals who reported sexual maltreatment were 27% more likely to be obese (BMI≥30; AOR = 1.27, 95% CI: 0.98–1.63) and 72% more likely to be extremely obese (BMI≥40) in adulthood (AOR = 1.72, 1.18–2.51) than those who did not. Individuals who reported physical maltreatment were 37% more likely to be extremely obese than those who did not (AOR = 1.37, 1.11–1.70). These relationships were true for males and females, and interaction terms by sex were not statistically significant. Adolescent depressive symptoms and BMI were statistically significant mediators between sexual and physical maltreatment and extreme obesity (p < .05), and between physical maltreatment and self-rated obesity (p < .05). Therefore, adolescent characteristics are mechanisms on the causal pathway between maltreatment and obesity in adulthood. Further research should explore these mechanisms.